Long-term cold acclimation extends survival time at 0°C and modifies the metabolomic profiles of the larvae of the fruit fly Drosophila melanogaster - Koštál, Vladimír; Korbelová, Jaroslava; Rozsypal, Jan; Zahradníčková, Helena; Cimlová, Jana; Tomčala, Aleš; Šimek, Petr (PloS one, 2011)
BACKGROUND: Drosophila melanogaster is a chill-susceptible insect. Previous studies on this fly focused on acute direct chilling injury during cold shock and showed that lower lethal temperature (LLT, approximately -5°C) exhibits relatively low plasticity and that acclimations, both rapid cold hardening (RCH) and long-term cold acclimation, shift the LLT by only a few degrees at the maximum. PRINCIPAL FINDINGS: We found that long-term cold acclimation considerably improved cold tolerance in fully grown third-instar larvae of D. melanogaster. A comparison of the larvae acclimated at constant 25°C with those acclimated at constant 15°C followed by constant 6°C for 2 d (15°C→6°C) showed that long-term cold acclimation extended the lethal time for 50% of the population (Lt(50)) during exposure to constant 0°C as much as 630-fold (from 0.137 h to 86.658 h). Such marked physiological plasticity in Lt(50) (in contrast to LLT) suggested that chronic indirect chilling injury at 0°C differs from that caused by cold shock. Long-term cold acclimation modified the metabolomic profiles of the larvae. Accumulations of proline (up to 17.7 mM) and trehalose (up to 36.5 mM) were the two most prominent responses. In addition, restructuring of the glycerophospholipid composition of biological membranes was observed. The relative proportion of glycerophosphoethanolamines (especially those with linoleic acid at the sn-2 position) increased at the expense of glycerophosphocholines. CONCLUSION: Third-instar larvae of D. melanogaster improved their cold tolerance in response to long-term cold acclimation and showed metabolic potential for the accumulation of proline and trehalose and for membrane restructuring.
Keywords: aminokyseliny; Drosophila melanogaster; analýza přežití; Freezing; aklimatizace; mastné kyseliny; Fatty Acids; Acclimatization; Polymers; Survival Analysis; zmrazování; Time Factors; larva; Animals; ženské pohlaví; polymery; zvířata; časové faktory; metabolismus sacharidů; Metabolome; Larva; metabolom; Female; Carbohydrate Metabolism; nízká teplota; Cold Temperature; Amino Acids